The inhbition of chromium effect in Saccharomyces cerevisiae thrive from grapefruit - Aslan, Abdullah; Can, Muhammed Ismail (Progress in Nutrition, 2015)
In this study, seven groups were composed. i: Control group, ii: K2Cr2O7 group, iii: 5 mM K2Cr2O7+ grapefruit juice (GFJ) group, iv: 10 mM K2Cr2O7 + GFJ group, v: 15 mM K2Cr2O7 + GFJ group, vi: 20 mM K2Cr2O7 + GFJ group, vii: 25 mM K2Cr2O7 + GFJ group. After sterilization, fruit juice (25%) and K2Cr2O7 were inserted different concentration to Saccharomyces cerevisiae (S. cerevisiae) cultures and the cultures were developed at 37°C for 1h, 3h, 5h and 24 hours (overnight). S. cerevisiae cell growth was determined by spectrophotometer, total protein changes was detected by SDS-PAGE electrophoresis and reckoned with biuret method. According to our studies results; cell growth rised in GFJ groups to which GFJ was taken in comparison to the positive control (K2Cr2O7) group at different growing times (1, 3, 5 and 24 hours) (p<0,05). As a result GFJ has a protecting for decrease the oxidative damage and increased cell growing and induced protein synthesis in S. cerevisiae culture.